Correction: Thermoelectric properties of CZTS thin films: effect of Cu–Zn disorder. Issue 25 (21st June 2021) - Isotta, E.; Syafiq, U.; Ataollahi, N.; Chiappini, A.; Malerba, C.; Luong, S.; Trifiletti, V.; Fenwick, O.; Pugno, N. M.; Scardi, P.
Abstract : Correction for 'Thermoelectric properties of CZTS thin films: effect of Cu–Zn disorder' by E. Isotta et al., Phys. Chem. Chem. Phys., 2021, DOI: ; 10.1039/d1cp01327k .